The use of NIRS for prediction of intake, digestibility, diet composition and faecal concentration of n-alkanes in sheep fed different proportions of lucerne and rye grass (Lolium rigidum) - Keli A.; Andueza D.; Baumont R.; Béchet G.; De Vega A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Sixteen sheep fed different proportions of lucerne and rye grass (100:0, 67:33, 33:67 and 0:100) were used to obtain regression equations for prediction, from the NIRS analysis of faeces, of dry matter intake (g/day or g/kg LW0.75), digestibility coefficients of dry matter (DMD), organic matter (OMD) and neutral detergent fibre (NDFD), lucerne consumed (% of the diet, g DM/day or g DM/kg LW0.75), and n-alkane concentrations in faeces. Sixteen pairs of faecal samples were collected in order to develop two calibration equations. Faeces were: (i) pooled (per animal) throughout a 7-day digestibility trial (S1); and (ii) taken daily from the rectum of the same animals at 9:00 hours (throughout the same 7 days of the digestibility trial) and pooled to obtain a unique sample per sheep (S2). All S2 equations had coefficients of determination in calibration (R2) higher than 0.66, whereas R2 in S1 equations was lower for the prediction of intake per kg metabolic weight (0.44), and OMD (0.46) and NDFD (0.56). The coefficients of determination in cross-validation (R2cv) were much lower than those in calibration, with equations derived from S2 showing again better performances for intake prediction. Accuracy of equations for prediction of digestibility coefficients was reached for neither S1 nor S2 samples. Diet composition and faecal concentration of most n-alkanes was more accurately predicted in both cases (R2cv>0.67).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)